MRI vs. CT for the Detection of Liver Metastases in Patients With Pancreatic Carcinoma: A Comparative Diagnostic Test Accuracy Systematic Review and Meta‐Analysis. Issue 1 (14th January 2020) - Alabousi, Mostafa; McInnes, Matthew DF; Salameh, Jean‐Paul; Satkunasingham, Janakan; Kagoma, Yoan K.; Ruo, Leyo; Meyers, Brandon M.; Aziz, Tariq; van der Pol, Christian B.
Abstract : Background: The detection of liver metastases is important for pancreatic cancer curative treatment eligibility. The data suggest that magnetic resonance imaging (MRI) is more sensitive than computed tomography (CT) for the diagnosis of pancreatic cancer liver metastases. However, MRI is not currently recommended in multiple published guidelines. Purpose: To perform a comparative diagnostic test accuracy systematic review and meta‐analysis comparing CT and MRI for pancreatic cancer liver metastases detection. Study Type: Systematic review and meta‐analysis. Data Sources: MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Scopus, and multiple radiology society meeting archives were searched until November 2018. Comparative design studies reporting on liver CT and MRI accuracy for detection of pancreatic cancer liver metastases in the same cohort were included. Field Strength: 1.5T or 3.0T. Assessment: Demographic, methodologic, and diagnostic test accuracy data were extracted. Risk of bias was assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS)‐2 tool. Statistical Tests: Accuracy metrics were obtained using bivariate random‐effects meta‐analysis. The impact of different covariates on accuracy estimates was assessed using a meta‐regression model. Covariates included modality, study design, tumor characteristics, risk of bias, and imaging protocols. Results: Fourteen studies including 987 patients with pancreatic cancer (205 with liver metastases) were included. Sensitivity for CT and MRI was 45% (confidence intervals [95% CI] 21–71%) and 83% (95% CI 74–88%), respectively. Specificity for CT and MRI was 94% (95% CI 84–98%) and 96% (95% CI 93–97%), respectively. The greater observed sensitivity of MRI was preserved in the meta‐regression model ( P = 0.01), while no difference in specificity was detected ( P = 0.16). CT sensitivity was highest for triphasic and quadriphasic examinations compared to single phase or biphasic protocols ( P = 0.03). Most studies were at high risk of bias. Data Conclusion: MRI is more sensitive than CT for pancreatic cancer liver metastases detection, accounting for confounding variables. Consideration of this finding in clinical practice guidelines is recommended. Level of Evidence: 3 Technical Efficacy Stage: 3